A review of Norwegian streptaster-bearing Astrophorida (Porifera: Demospongiae: Tetractinellida), new records and a new species - Cárdenas, Paco; Rapp, Hans Tore (Zootaxa, 2012)
We report and describe new material of streptaster-bearing Astrophorida sponges collected in Norway: Characellapachastrelloides, Pachastrella nodulosa sp. nov., Poecillastra compressa, Vulcanella cf. aberrans, Thenea abyssorum,Thenea levis, Thenea muricata and Thenea valdiviae. Because many of these species were described in the end of the 19thcentury their original descriptions are often incomplete. The Norwegian specimens are the basis for a revision of themorphology, taxonomy and distribution of these species. These are the first records of C. pachastrelloides and V. cf.aberrans from the Norwegian coast. Pachastrella nodulosa sp. nov. differs from Pachastrella monilifera by (i) its knobbysurface and (ii) the absence of large oxeas, (iii) its amphiasters have on average less actines and are less spiny, finally (iv)microxeas are rare and with a distinct morphology (although there is some doubt concerning their origin). In the presentstudy, Characella tuberosa (from South Africa), Pachastrella abyssi (from the North-West Atlantic) and Thenea schmidti(from the North-East Atlantic) are resurrected. To help their future identifications, all the Norwegian species describedwere associated with DNA barcodes: a cytochrome c oxidase subunit I (COI) gene partial fragment and/or a 28S ribosomalgene partial fragment (C1–D2 domains). Furthermore, a key to the streptaster-bearing Astrophorida of the North-East Atlantic and the Mediterranean Sea is also given (lithistids not included).Nous signalons la présence et décrivons des spécimens d’Astrophorida à streptasters nouvellement récoltés en Norvège:Characella pachastrelloides, Pachastrella nodulosa sp. nov., Poecillastra compressa, Vulcanella cf. aberrans, Theneaabyssorum, Thenea levis, Thenea muricata et Thenea valdiviae. Plusieurs de ces espèces ont été décrites de manièreincomplète à la fin du 19ème siècle. Les spécimens norvégiens sont l’occasion de réviser la morphologie, la taxonomie etla distribution de ces espèces. C’est la première fois que C. pachastrelloides et V. cf. aberrans sont mentionnés sur la côtenorvégienne. Pachastrella nodulosa sp. nov. se distingue de Pachastrella monilifera par (i) sa surface noduleuse et (ii)l’absence de grands oxes, (iii) ses amphiasters ont en moyenne moins d’actines et sont moins épineux, enfin (iv) lesmicroxes sont rares et ont une morphologie distincte (bien qu’il y ait encore des doutes sur leur origine). Au cours de notreétude, Characella tuberosa (d’Afrique du Sud), Pachastrella abyssi (de l’Atlantique Nord-Ouest) et Thenea schmidti (del’Atlantique Nord-Est) sont ressuscités. Afin d’aider leurs identifications futures, toutes les espèces de Norvège décritesont été associées à des code-barres moléculaires: un fragment partiel du gène de la sous-unité I du cytochrome c oxydase(COI) et/ou un fragment partiel du gène ribosomique 28S (domaines C1-D2). De plus, une clé pour identifier les Astrophorida à streptasters de l’Atlantique Nord-Est et de Méditerrannée est également fournie (lithistides non inclus).